Computational modelling of novel permanent magnetic designs - Hilton, James (Trinity College (Dublin, Ireland). School of Physics, 2005)
Moderm permanent magnetic materials provide unique design opportunities as their low susceptibility makes them effectively transparent to external magnetic fields. This also simplifies the calculation of magnetic fields in devices incorporating them. We have developed two software programs to simulate the magnetic field from arrays of such permanent magnets. The first is based on the magnetic charge model, and the second uses a magnetostatic finite element method.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin